Kidney Transplantation in Small Children: Association Between Body Weight and Outcome—A Report From the ESPN/ERA-EDTA Registry. Issue 3 (March 2022) - Boehm, Michael; Bonthuis, Marjolein; Aufricht, Christoph; Battelino, Nina; Bjerre, Anna; Edvardsson, Vidar O.; Herthelius, Maria; Hubmann, Holger; Jahnukainen, Timo; de Jong, Huib; Laube, Guido F.; Mattozzi, Francesca; et al.
Abstract : Background: Many centers accept a minimum body weight of 10 kg as threshold for kidney transplantation (Tx) in children. As solid evidence for clinical outcomes in multinational studies is lacking, we evaluated practices and outcomes in European children weighing below 10 kg at Tx. Methods: Data were obtained from the European Society of Paediatric Nephrology/European Renal Association and European Dialysis and Transplant Association Registry on all children who started kidney replacement therapy at <2.5 y of age and received a Tx between 2000 and 2016. Weight at Tx was categorized (<10 versus ≥10 kg) and Cox regression analysis was used to evaluate its association with graft survival. Results: One hundred of the 601 children received a Tx below a weight of 10 kg during the study period. Primary renal disease groups were equal, but Tx <10 kg patients had lower pre-Tx weight gain per year (0.2 versus 2.1 kg; P  < 0.001) and had a higher preemptive Tx rate (23% versus 7%; P  < 0.001). No differences were found for posttransplant estimated glomerular filtration rates trajectories ( P  = 0.23). The graft failure risk was higher in Tx <10 kg patients at 1 y (graft survival: 90% versus 95%; hazard ratio, 3.84; 95% confidence interval, 1.24-11.84), but not at 5 y (hazard ratio, 1.71; 95% confidence interval, 0.68-4.30). Conclusions: Despite a lower 1-y graft survival rate, graft function, and survival at 5 y were identical in Tx <10 kg patients when compared with Tx ≥10 kg patients. Our results suggest that early transplantation should be offered to a carefully selected group of patients weighing <10 kg.